2022
DOI: 10.3389/fmicb.2022.975344
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic and functional analyses of Paenibacillus peoriae ZBSF16 with biocontrol potential against grapevine diseases, provide insights into its genes related to plant growth-promoting and biocontrol mechanisms

Abstract: Paenibacillus peoriae is a plant growth-promoting rhizobacteria (PGPR) widely distributed in various environments. P. peoriae ZBFS16 was isolated from the wheat rhizosphere and significantly suppressed grape white rot disease caused by Coniella vitis. Here, we present the complete genome sequence of P. peoriae ZBFS16, which consists of a 5.83 Mb circular chromosome with an average G + C content of 45.62%. Phylogenetic analyses showed that ZBFS16 belongs to the genus P. peoriae and was similar to P. peoriae ZF3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The genome of JJ-246 T also shares a gene cluster trpEDCFBA (CAH1218260-CAH1218273; Table S5), related to the production of indole-3-acetic acid (IAA), an important phytohormone known to stimulate plant growth (e.g. Yuan et al 2022 ; Shao et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genome of JJ-246 T also shares a gene cluster trpEDCFBA (CAH1218260-CAH1218273; Table S5), related to the production of indole-3-acetic acid (IAA), an important phytohormone known to stimulate plant growth (e.g. Yuan et al 2022 ; Shao et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The four pst genes ( pstS , pstC , pstA , and pstB ) from the phosphate-specific transport (Pst), an important bacterial transport system for phosphate, were also present in all genomes analyzed. Previously, Yuan et al ( 2022 ) and Jiang et al ( 2023 ) had also reported the presence of pstABCS in the plant growth-promoting bacteria Paenibacillus peoriae and Saccharibacillus brassicae , respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Various studies have used whole-genome sequencing and comparative analysis to delve into the intricate bacterial mechanisms that contribute to the promotion of plant growth. Examples include investigations on Bacillus pumilus strain SF-4 (Iqbal et al 2021 ), Bacillus subtilis BS87 (Chandra et al 2021 ), Saccharibacillus brassicae ATSA2 (Jiang et al 2023 ), and Paenibacillus peoriae ZBSF16 (Yuan et al 2022 ). Numerous studies highlight the plant growth-promoting abilities of Lysinibacillus (Ahsan and Shimizu 2021 ; Naureen et al 2017 ; Pantoja-Guerra et al 2023 ; Sahu et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paenibacillus species are increasingly associated with plant growth promotion (Wang et al, 2023) as well as biocontrol capabilities against e.g., Coniella vitis (white rot of grape) and Fusarium spp. (Yuan et al, 2022), among others. Like strain TP18m, other P. parafulva strains also display antimicrobial activities (Abanda-Nkpwatt et al, 2006; Kakembo and Lee, 2019).…”
Section: Discussionmentioning
confidence: 99%